Inclusive Monetary Policy: How Tight Labor Markets Facilitate Broad-Based Employment Growth - Nittai K. Bergman; David Matsa; Michael Weber; Michael Weber (Center for Economic Studies and ifo Institute (CESifo), 2022)
This paper analyzes the heterogeneous effects of monetary policy on workers with differing levels of labor force attachment. Exploiting variation in labor market tightness across metropolitan areas, we show that the employment of populations with lower labor force attachment—Blacks, high school dropouts, and women—is more responsive to expansionary monetary policy in tighter labor markets. The effect builds up over time and is long lasting. We develop a New Keynesian model with heterogeneous workers that rationalizes these results. The model shows that expansionary monetary shocks lead to larger increases in the employment of less attached workers when the central bank follows an average inflation targeting rule and when the Phillips curve is flatter. These findings suggest that, by tightening labor markets, the Federal Reserve's recent move from a strict to an average inflation targeting framework especially benefits workers with lower labor force attachment.
Keywords: E12; E24; E31; E43; E52; E58; J24; 330; monetary policy; labor markets; heterogeneous agents; federal reserve